PENGARUH PENGGUNAAN MEDIA TANGGA KONVERSI TERHADAP PENGUASAAN PENGUKURAN PANJANG SISWA KELAS 4 SDN SATAK 2 PUNCU - Putri, Ramadhana Khoiri; Ita Kurnia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on the results of observations that have been carried out in class 4 of SDN Satak 2 Puncu, it can be seen that teachers do not use learning media, the methods used by teachers are less varied, only using lecture methods, student competencies in the material on measuring length are lacking or below the KKM. Based on these problems, a study was conducted with the title of the effect of using conversion ladder media on the mastery of length measurement of class 4 students of SDN Satak 2 Puncu. The formulation of the problem in this study is 1) How does the use of conversion ladder media affect the mastery of length measurement of class 4 students of SDN Satak 2 Puncu, 2) How does the use of ruler media affect the mastery of length measurement of class 4 students of SDN Satak 2 Puncu, and 3) Is there a difference in the effect of using conversion ladder media and ruler media on the mastery of length measurement of class 4 students of SDN Satak 2 Puncu. This research is a quantitative research. The subjects of this study were 15 students of class 4 of SDN Satak 2 Puncu and 20 students of class 4 of SDN Pakis. The data collection technique used a test instrument. The data analysis techniques used were normality test, homogeneity test, and t-test. Based on the results of this study, it can be concluded as follows. 1) There is an effect of using conversion ladder media on the mastery of length measurement of grade 4 students of SDN Satak 2 Puncu with the results obtained tcount -14.666 < ttable - 1.761 with a significance level of 5%. 2) There is an effect of using ruler media on the mastery of length measurement of grade 4 students of SDN Pakis with the results obtained tcount -8.718 < ttable -1.729 with a significance level of 5%. There is a difference in the effect of using conversion ladder media and ruler media on the mastery of length measurement of grade 4 students of SDN Satak 2 Puncu. This is evidenced by the results of tcount -8.186 < ttable -1.692 with a significance level of 5%.